2016
DOI: 10.1038/srep20361
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulosic ethanol production by starch-base industrial yeast under PEG detoxification

Abstract: Cellulosic ethanol production from lignocellulosic biomass offers a sustainable solution for transition from fossil based fuels to renewable alternatives. However, a few long-standing technical challenges remain to be addressed in the development of an economically viable fermentation process from lignocellulose. Such challenges include the needs to improve yeast tolerance to toxic inhibitory compounds and to achieve high fermentation efficiency with minimum detoxification steps after a simple biomass pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 44 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…The low μ max values in the present study may be due to the cell growth inhibition by ethanol and/or inhibitory compounds generated during PRs pretreatment. It has been reported that the presence in the fermentation medium of phenolics at 2.0 g/L negatively affects both cell viability of S. cerevisiae and ethanol production (Liu et al, 2016). In the present study, the initial concentration of phenolic compounds was about 2.0 g/L and remained almost constant during fermentation of S. cerevisiae .…”
Section: Resultsmentioning
confidence: 99%
“…The low μ max values in the present study may be due to the cell growth inhibition by ethanol and/or inhibitory compounds generated during PRs pretreatment. It has been reported that the presence in the fermentation medium of phenolics at 2.0 g/L negatively affects both cell viability of S. cerevisiae and ethanol production (Liu et al, 2016). In the present study, the initial concentration of phenolic compounds was about 2.0 g/L and remained almost constant during fermentation of S. cerevisiae .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it is possible to observe that 28.99% of the reducing sugars present in the medium were not consumed. Although the pretreatment processes of the lignocellulosic biomass employed in this work are widely used strategies, they have the disadvantage of generating toxic compounds to fermenting organisms, such as phenolic compounds, guaiacol, levulinic acid, furfural and 5-hydroxymethyl furfural (Varanasi et al, 2013;Liu et al, 2016). The presence of such substances may have inhibited the activity of S. cerevisiae, making it impossible to deplete the substrate offered, since the samples were not detoxified to remove these substances.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to observe in the fermentation experiment with Saccharomyces cerevisiae that 28.99% of the reducing sugars present in the medium were not consumed. The pretreatment processes of lignocellulosic biomasses employed in this work are widely used strategies; however, they have the disadvantage of generating toxic compounds to fermenting organisms, such as phenolic compounds, guaiacol, levulinic acid, furfural and 5-hydroxymethylfurfural ( Varanasi et al, 2013 ; Liu et al, 2016 ). Although the pre-treated endocarp was rinsed with distillate water before enzymatic scarification, Zhang et al (2010) indicate that this method is not efficient for total removal of toxic compounds impregnated in the biomass.…”
Section: Discussionmentioning
confidence: 99%